Analisis Konten Edukasi IPA di Media Sosial TikTok sebagai Potensi Sumber Belajar Mandiri - Inung Diah Kurniawati; Yoga Prisma Yuda; Krisma Lofitasari (Jurnal Multidisiplin Indonesia, 2026)
The rise of social media has introduced various alternative learning resources that offer flexible access, including the TikTok platform. The diverse science educational content available on the platform has the potential to support independent student learning; however, its quality and characteristics require further examination. This study aims to analyze the characteristics of science educational content on TikTok and identify its potential as a resource for independent learning. A qualitative approach utilizing content analysis was employed. The study examined 40 science educational videos selected based on specific criteria: covering science topics, using the Indonesian language, being educational in nature, and demonstrating high levels of interaction. The results indicate that physics was the most frequently presented subject (50%), followed by biology (42.5%) and chemistry (7.5%). Most content was delivered concisely, utilizing a combination of text, narration, animation, and experimental demonstrations, thereby enhancing engagement and facilitating conceptual understanding. Regarding quality, 55% of the videos presented science concepts consistent with scientific references, while 45% carried a risk of fostering misconceptions due to the simplification of concepts. The findings demonstrate that TikTok holds potential as a resource for independent learning due to its accessibility, engaging nature, contextual relevance, and ability to boost learning motivation. Nevertheless, its utilization requires digital literacy skills and content curation by educators to ensure that the information obtained remains accurate and aligned with learning objectives.